Molecular cloning of TaMATE2 homoeologues potentially related to aluminium tolerance in bread wheat (Triticum aestivum L.) - García Oliveira, A.L.; Benito, C.; Guedes-Pinto, H.; Martins Lopez, P. (Wiley, 2018)
Recently, members of the MATE family have been implicated in aluminium (Al) tolerance by facilitating citrate efflux in plants. The aim of the present work was to perform a molecular characterisation of the MATE2 gene in bread wheat. Here, we cloned a member of the MATE gene family in bread wheat and named it TaMATE2, which showed the typical secondary structure of MATE‐type transporters maintaining all the 12 transmembrane domains. Amplification in Chinese Spring nulli‐tetrasomic and ditelosomic lines revealed that TaMATE2 is located on the long arm of homoeologous group 1 chromosomes. The transcript expression of TaMATE2 homoeologues in two diverse bread wheat genotypes, Barbela 7/72/92 (Al‐tolerant) and Anahuac (Al‐sensitive), suggested that TaMATE2 is expressed in both root and shoot tissues of bread wheat, but mainly confined to root rather than shoot tissues. A time‐course analysis of TaMATE2 homoeologue transcript expression revealed the Al responsive expression of TaMATE2 in root apices of the Al‐tolerant genotype, Barbela 7/72/92. Considering the high similarity of TaMATE2 together with similar Al responsive expression pattern as of ScFRDL2 from rye and OsFRDL2 from rice, it is likely that TaMATE2 also encodes a citrate transporter. Furthermore, the TaMATE2‐D homoeologue appears to be near the previously reported locus (wPt0077) on chromosome 1D for Al tolerance. In conclusion, molecular cloning of TaMATE2 homoeologues, particularly TaMATE2‐D, provides a plausible candidate for Al tolerance in bread wheat that can be used for the development of more Al‐tolerant cultivars in this staple crop.